Tomb security in ancient Egypt from the Predynastic to the Pyramid Age - Clark, Reg (Archaeopress, 2016)
Egyptians went to great lengths to protect their dead from the omnipresent threat of robbery by incorporating specially developed architectural features in their tombs. However, the architecture of tomb security has rarely been studied as a subject in its own right and is usually treated as a secondary topic in publications of a scholarly nature, which tend to regard its role as incidental to the design of the tomb rather than perhaps being the driving force behind it. This issue had been raised in the early Twentieth Century by Reisner (1908: 11), who suggested that the rapid evolution of Egyptian tomb substructures was as a result of the desire for tomb security and more ostentatious tombs, rather than a development spurred by religious or funerary practices.